1994
DOI: 10.1139/g94-113
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite polymorphism in Dioscorea tokoro, a wild yam species

Abstract: Six microsatellite loci were characterized in Dioscorea tokoro, a wild yam species in East Asia. All six loci were polymorphic in a sample of 23 individuals from natural populations in Japan. The microsatellite loci displayed many alleles (6.2 alleles per locus on average), and the observed heterozygosity (Ho = 0.54) as well as expected heterozygosity (He = 0.68) were high. The heterozygosities were far more than that previously detected by allozyme analysis of D. tokoro (Ho = 0.23, He = 0.28). Five microsatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 0 publications
8
33
0
2
Order By: Relevance
“…Microsatellite loci are a demonstrated rich source of highly polymorphic genetic markers in an ever-increasing number of organisms, and are promising markers for the detection of genetic variation in species, while allozyme analysis has revealed only low levels of variation (Saghai-Maroof et al 1994;Terauchi and Konuma 1994;Lehmann et al 1996;Sanchez et al 1996;Estoup et al 1998;Meglecz et al 1998;Streiff et al 1998;Dje et al 1999;Sun et al 1999;Lemaire et al 2000). For example, in the yam (Dioscorea tokoro), Terauchi and Konuma (1994) found that microsatellites show higher levels of genetic variability than allozymes with respect to heterozygosity. In the current study, all the microsatellite loci surveyed were polymorphic with four to 14 alleles per locus, and an average of 3.1 alleles per locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellite loci are a demonstrated rich source of highly polymorphic genetic markers in an ever-increasing number of organisms, and are promising markers for the detection of genetic variation in species, while allozyme analysis has revealed only low levels of variation (Saghai-Maroof et al 1994;Terauchi and Konuma 1994;Lehmann et al 1996;Sanchez et al 1996;Estoup et al 1998;Meglecz et al 1998;Streiff et al 1998;Dje et al 1999;Sun et al 1999;Lemaire et al 2000). For example, in the yam (Dioscorea tokoro), Terauchi and Konuma (1994) found that microsatellites show higher levels of genetic variability than allozymes with respect to heterozygosity. In the current study, all the microsatellite loci surveyed were polymorphic with four to 14 alleles per locus, and an average of 3.1 alleles per locus.…”
Section: Discussionmentioning
confidence: 99%
“…Since Condit and Hubbell (1991) first noted that microsatellite analysis has great potential for understanding plant population genetics in natural populations, it is now widely used in population and conservation genetic studies (e.g. Bruford and Wayne 1993;Saghai-Maroof et al 1994;Terauchi and Konuma 1994;Chase et al 1996a, b;Inna et al 1997;van Treuren et al 1997;Aldrich et al 1998;Provan et al 1999;Olsen and Schaal 2001). Recently, hundreds of microsatellites from rice have been developed, mapped and published (Wu and Tanksley 1993;Akagi et al 1996;Panaud et al 1996;Chen et al 1997;McCouch et al 1997;Cho et al 2000;Temnykh et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Jelinski and Cheliak (1992) (Terauchi and Konuma, 1994) yielding an observed H=0.54 compared to H=0.23 with allozymes. These findings are also consistent with what has been found for animal populations (e.g., see Scribner et al, 1994).…”
Section: The Use Of Synthetic Probes For Vntr Loci In Plantsmentioning
confidence: 88%
“…Molecular markers of DNA can be used to reveal the differences, correlation, and genetic relationships among different varieties of species (Hou et al, 2006). For example, Terauchi and Konuma (1994) analyzed a wild yam species with microsatellite polymorphisms, Mignouna et al (2002) constructed a genetic linkage map of guinea yam and water yam with amplified fragment length polymorphism markers, and Zhou et al (2005) analyzed the genetic diversity of 28 cultivar varieties of D. opposita Thunb. using inter-simple sequence repeat markers.…”
Section: Introductionmentioning
confidence: 99%